Motor ultra-sônico linear com geometria tubular - Pippi, Rafael Silva (2008)
This work presents the study on a linear ultrasonic motor with tubular geometry for linear displacements. Similar topologies, reported elsewhere, are conceived for producing rotary motions. Due to some particular characteristics of this geometry, not explored yet, a new study on interaction between resonance modes in a hollow cylinder for linear movement generation is proposed. In order to experimentally investigate the resonance modes in tubular stators, a proof of concept prototype was built and tested. The prototype consisted of a internally toothed phosphore bronze tube, excited by two PZT rings. Several types of mobile axes, with one or more solid cylinders of aluminum or stainless steel, were employed. The methodology of test consisted of changing geometric parameters, properties of materials, sweeping driving conditions, and observing the respective movement on the shaft. Tests showed the production of linear and/or angular movements, with maximum speeds of 0,07m/s, but with little uniformity and repeatability. The lack of conclusive hypothesis on the stability issue, based only on experimental set of results, has led to a reassessment of the methodology of investigation, including additional analysis tools for the characterization of the device. So, a simple analytical modeling of the stator was formulated to set up a project methodology. Despite its simplicity and limitations, the analytical model allows a first order approximation for resonance modes, and relates them to the constructive parameters of the stator. In order to take the influence of the factors neglected in the analytical modeling into account, the analysis was complemented with finite element method (FEM) simulations. The deformation profiles of the stator to the 21st resonance mode were analyzed using FEM. With the results, it is possible to predict the behavior of the resonance frequencies, and the corresponding deformations they produce on the teeth, for each stator configuration. The most important result of this analysis is to show the relationship between aspect ratio of ellipsoidal trajectory on the stator teeth and the geometry of the stator. This allows a conclusive diagnosis on the inefficiency of the built prototype: The small amplitude of the longitudinal component of traveling deformation wave. An analysis of simulations results has lead to a design methodology for this new type of motor. The results showed that if the stator is redesigned according to the proposed methodology, it would be able to produce longitudinal deformations of 2.6 μm, with ceramics driven at 35.3 V. If Compared to simulations of the prototyped stator the new project exhibits an increase of 90% for radial deformation components of, and 3600% for the longitudinal components, indicating that if the new design was implemented, it could achieve much higher efficiency in movement production.